Developing a Framework for the Analysis and Evaluation of Quran Translations - Mohammad Beigi, Shahrokh; Rashidi, Naser; Zolfaghari, Fatemeh (LANGUAGE ART, 2022)
The purpose of the current study is to develop a comprehensive conceptual model for the analysis and evaluation of translations of the Quran. Seven Arabic-to-English translations of the Quran are analyzed in a descriptive-analytic way, considering the intra-textual semantic, discursive and syntactic relations. The analysis indicated that in translating and evaluating the translations of the Quran, the translators and evaluators might consider some significant features. These features and components are punctuation, interpretability, and structural aspects of language, loyalty to the meaning of the source text, style, and the effect of different readings of the Quran, and the translators’ record, the revelation and its subcategories. The study also shows that translation of the Quran is possible and acceptable, on the condition that the translator follows the given set of principles.